Peculiarities of the social representation of emotions and feelings of mentally handicapped person - Gailienė, Irena; Ruškus, Jonas (Psichologija, 2000)
This article presents peculiarities of the social representation of emotions and feelings of mentally handicapped persons.
Keywords: social representation; mentally handicapped person; emotions; feelings